Erythropoiesis and Iron Exchange in Burns - E. N. Barkova; L. F. Balabanova; Ye. V, Zhdanova; V. V. Kuznetsov; Ye. V. Nazarenko (Общая реаниматология, 2007)
The purpose of the study was to elucidate the specific features of the biorhythms of iron exchange and erythropoiesis in thermal injury and to define their role in the pathogenesis of anemia.Materials and methods. Seventy-five patients aged 32 to 45 years, who had extensive (up to 50% of the body’s surface) superficial (second-to-third degree) thermal burns, were examined. A control group comprised 108 donors aged 25—35 years. Examinations were made four times daily on days 1, 2, 3, 7, 14, 21, 28, 38, 48, 60 after injury. The authors studied daily changes in the titers of erythropoietin (EP), ferritin (F), serum iron concentrations (SIC), MDA, the populations of the ineffective, normal, and terminal types of erythron kinetics (by the activity of glucose-6-phosphate dehydrogenase (G-6-PDG)).Results. The progressive reduction in the levels of erythro-cytes and hemoglobin, which most intensive during three weeks after injury has been found to correlate with the rise in the population of microcytes with a low activity of G-6-PDG and shorter survival in the presence of significantly elevated concentrations of F, EP, and MDA in the evening. In the morning, the production of a highly active population of macrocytes, the progeny of terminal erythropoiesis is increased, which causes a decrease in SIC and levels its circadian rhythm due to the higher uptake of the trace.Conclusion. The surplus of tissue iron pool due to hyperphagocytosis of short-lived erythrocytes, as well as high EP titer-induced inhibition of apoptosis have been ascertained to be the leading mechanisms of burn-related anemia. Their basis is the stimulation of the alternative (terminal and ineffective) types of erythron kinetics.